Pemberdayaan UMKM Desa Pangebatan melalui Digital Marketing untuk Optimalisasi Pemasaran Tepung Mocaf - Desty Rakhmawati; Zanuar Rifai (Universitas Pahlawan Tuanku Tambusai, 2026)
Pangebatan Village in Banyumas Regency, Central Java, is an extreme priority village with a 37% poverty rate. The potential of cassava as a leading commodity (50.99% of Karanglewas District's production) has not been optimally utilized due to limitations in processing and marketing. The Mocaf Production House MSME faces serious obstacles: a lack of professional marketing staff and a lack of digital marketing strategies. This community service program aims to empower MSMEs through digital marketing training and mentoring to expand market reach. The methods used include focus group discussions (FGDs), outreach, intensive training (Facebook Ads, Instagram Ads, Google Business), implementation mentoring, and monthly evaluations. As a result, two professional marketing staff were formed, the MSME has a verified website and social media accounts, sales increased by 40%, and the marketing network expanded to three districts. This program contributes to improving community welfare and optimizing local potential.